Detection of premature stop codons leading to truncated internalin A among food and clinical strains of Listeria monocytogenes - Silva, Margarida Ferreira da (2017)
Listeria monocytogenes is a food-borne pathogen responsible for outbreaks and sporadic cases of listeriosis, a severe invasive disease. Internalin A (InlA) a protein encoded by inlA has a key role in the mechanism of pathogenesis in L. monocytogenes infection, specifically in the invasion of human intestinal epithelial cells. Studies on inlA have shown that mutations leading to premature stop codons (PMSCs) occur naturally and are associated with impaired virulence of L. monocytogenes strains. Increasing evidence suggests that inlA PMSCs mutations are frequent in strains from foods, but rare among clinical isolates. In this study, 22 L. monocytogenes strains collected in Portugal from the processing environment of a bakery industry (n = 1), different food products (n = 10) and human clinical cases (n = 11) were analysed for mutations in inlA and invasion efficiency in Caco-2 cells. Sequencing revealed previously reported mutations types leading to PMSCs in three food and one clinical strain presenting different molecular serotypes (i.e., IIa, IIb and IIc). The remaining 18 isolates did not show PMSCs in inlA. The four strains with PMSCs in inlA presented lower invasiveness efficiencies in Caco-2 cells (below 8.9%) when compared to the control strain (full-length InlA). In addition, one clinical isolate showed reduced invasion efficiency but no PMSCs in inlA. This isolate showed increased inlA transcript levels to that obtained for the laboratory control strain. Our data support the hypothesis that L. monocytogenes isolated from food have attenuated invasion due to the presence of inlA PMSCs. This information would be critically needed for adequate risk-assessments of the foodborne illness burden associated with L. monocytogenes strains.